MODEL STRATEGI CITY BRANDING, ELECTRONIC WORD OF MOUTH, TERHADAP KEPUTUSAN BERKUNJUNG YANG DIMEDIASI OLEH CITY IMAGE DALAM MEWUJUDKAN SMART CITY MENUJU KOTA TANGERANG KELAS DUNIA - dodi subagia (Jurnal MoZaiK, 2020)
This study aims to determine the effect of e-WOM, city branding on visiting decisions mediated by the image of the city in realizing a smart city towards the world-class city of Tangerang. This research model becomes very important to provide input to the Tangerang City government in improving the city image of the international community. Research samples from 169 people who have visited Tangerang City and lived in Jakarta, Bogor, and Bekasi, this study uses smartPLS 3 analysis. The results of this study found new findings from the influential city branding model of e-Wom. mediated by Citra City showed significant results and had an impact on increasing tourist visiting decisions. This research deserves to be the basis of a roadmap for the Tangerang City Government to pay attention to the importance of developing a city image model and to provide opportunities for researchers to study it in the future..